Optimal Location and Sizing of Distributed Generation Unit Using Human Opinion Dynamics Optimization Technique - Mahajan, Shreya; Vadhera, Dr. Shelly (Distributed Generation & Alternative Energy Journal, 2018)
The demand of electricity is soaring rapidly. Distributed genera- tion (DG) is one of the most suitable alternatives to fulfill this swelling demand of energy. DG is a small scale generation which is directly in- stalled in the distribution network or at load centre. Optimal allocation of DG is a vital factor in improving the voltage profile of the system and in reduction of total power losses. In this article, a detailed study of three different methods for DG allocation and sizing has been discussed. The first method is based on Newton Raphson load flow based technique to deduce the optimal location of DG in two different IEEE bus systems in MATLAB software. The next methodology is based on particle swarm optimization (PSO) technique where a multi-objective function is being minimized. The objective function has been modified and PSO has been implemented to attain optimal size and location of DG unit. The third method considered is based on human opinion dynamics evolution- ary multi-objective optimization technique which is used to obtain the best possible size and location of DG unit in IEEE 14 and IEEE 30 bus systems. The human opinion dynamics method shows superiority in minimizing the size and location muti-objective function, over the other methods considered herein.